Efeito de uma intervenção educativa para a redução de peso em adolescentes na Atenção Primária à Saúde - BARROSO, Raidanes Barros (2021)
Introduction: Overweight has progressively increased in adolescents, due to the high consumption of processed foods, decreased consumption of fruits and vegetables, and sedentary lifestyle. The incorporation of educational technologies that prevent injuries and promote the health of these young people can collaborate to sensitize them to adhere to healthy habits, and primary health care is conducive to carrying out interventions. Objective: To evaluate the effect of an educational intervention for weight reduction in adolescents in primary health care. Method: Quasi-experimental, self-controlled study, of the before and after type, developed between November 2020 and July 2021, in three Basic Health Units in the city of Imperatriz - MA. The sample included 12 adolescents for convenience, following eligibility criteria, namely: age between 10 and 19 years, both genders and overweight in the z score between +1 and +3, according to the BMI for age indicator. Data collection involved three steps: 1. Pre- test, adolescents answered questions about social and economic characteristics, eating habits and physical activity, in a semi-structured questionnaire, and anthropometric measurements were measured before the intervention; 2. Intervention, which took place in five weekly meetings in which the themes of eating and physical activity were addressed, through an expository-dialogued class, workshops and a conversation circle; 3. After the test, the adolescents were measured again in the anthropometric parameters and answered the questions asked before the intervention, in order to observe if there was any change in the group's knowledge and eating habits, and intention to change their behavior in the physical activity category and in anthropometric measurements. In the data analysis, anthropometric measures, blood pressure, general knowledge about diet and level of physical activity were compared, before and after the intervention, using Student's t and Wilcoxon Pareado tests. Eating habits and level of knowledge in the pre- and post-tests were evaluated using the McNemar and McNemar-Bowker tests. Results: Most participants were female (75%), with a mean age of 12.5 years (SD± 1.6). The analysis of the nutritional status of overweight adolescents, according to BMI z-scores for age, did not reveal relevant changes after the intervention, regarding overweight (83.3% - 75%) and obesity (16.6% - 16 .6%). There was a positive correlation between systolic blood pressure and height (p=0.01), and between diastolic blood pressure and weight (p=0.04), abdominal (p=0.05) and suprailiac (p=0.02) folds . The assessment of eating habits after the educational intervention did not show a statistically significant change. There was a 63% increase in the adolescents' general knowledge about food after the intervention. There was no statistical significance on the intention to change physical activity behavior after the intervention. Conclusion: The educational intervention for weight reduction in adolescents in primary health care showed an increase in the daily consumption of fruits, and in general knowledge about diet and diseases related to inadequate nutrition. Furthermore, after the intervention, there were no changes in the adolescents' behavior regarding the practice of physical activity and anthropometric parameters.